2012
DOI: 10.12938/bmfh.31.59
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary L-arabinose on the Intestinal Microbiota and Metabolism of Dietary Daidzein in Adult Mice

Abstract: This study examined the effects of L-arabinose on mouse intestinal microbiota and urinary isoflavonoids. Male mice were randomly divided into two groups: those fed a 0.05% daidzein–2.5% L-arabinose diet (AR group) and those fed a 0.05% daidzein control diet (CO group) for 28 days. The amounts of daidzein detected in urine were significantly lower in the AR group than in the CO group. The ratio of equol/daidzein was significantly higher in the AR group (p<0.01) than in the CO group. The composition of caecal fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…However, several studies focussed on how other substrates modulate the IM, and, in turn, affect daidzein metabolism. Three studies in mice investigated how other dietary components such as xylitol, arabinose, or rice bran oil may change the gut microbial composition which, in turn, may also affect daidzein metabolism [ 95 97 ]. In all studies, two groups of mice were fed either 0.05% daidzein in the diet alone or together with 5% xylitol, 10% rice bran oil (in this case the daidzein group also received 10% lard as control) or 2.5% arabinose in their diets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies focussed on how other substrates modulate the IM, and, in turn, affect daidzein metabolism. Three studies in mice investigated how other dietary components such as xylitol, arabinose, or rice bran oil may change the gut microbial composition which, in turn, may also affect daidzein metabolism [ 95 97 ]. In all studies, two groups of mice were fed either 0.05% daidzein in the diet alone or together with 5% xylitol, 10% rice bran oil (in this case the daidzein group also received 10% lard as control) or 2.5% arabinose in their diets.…”
Section: Resultsmentioning
confidence: 99%
“…l -Arabinose-fed mice had lower urinary amounts of daidzein and the ratio of equol/daidzein was significantly compared to the control group. The abundance of Prevotella and Lactobacillales were significantly lower in the arabinose group [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current studies also only establish correlation not causation. One study in mice showed that dietary supplementation with daidzein and arabinose resulted in lower relative amounts of Prevotella but increased the ratio of equol/daidzein compared to supplementation of daidzein alone, suggesting that providing both daidzein and arabinose increases gut bacteria capable of metabolizing daidzein to equol 54 . Comparably, no other studies have shown that the other bacteria listed above can serve as equol producers.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 23 biomarkers identified in the CSB, arabinose and α- and γ-tocopherol ( Table 4 ) have been previously reported in soybean literature ( 43 ). Arabinose may be converted into short-chain FAs by bacteria to support healthy enterocyte metabolism, bolster gut mucosal immunity, and beneficially modulate the microbiome ( 80 82 ). α- and γ-Tocopherol possess broad-spectrum antioxidant and immunomodulatory activities ( 42 ).…”
Section: Discussionmentioning
confidence: 99%